Luthers Magnificat - Reuver, Arie de (Theologia reformata, 2024)
Luther's pastoral commentary on Mary's Magnificat is characteristic of his theology and spirituality. This article examines how Luther understood the ancient veneration of Mary that was in vogue in his own time, and how his explanation differs from the established opinion. The latter is explained and substantiated by a sketch of the vision of experientia and humilitas that unfold in the Magnificat. This essay shows that Luther's Mariology is marked by the dialectic of his theology of the cross.